Theories and Models of Consumer Behaviour Relating to the Purchase Intention Regarding Food Products – A Critical Review - Naskręt, Mikołaj; Pierański, Bartłomiej (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
In the current dynamically changing environment and unstable economy, there are a number of factors that are changing consumers’ intention to buy food. Due to that fact, there is still a need for further usage and adoption of available consumer behaviour models and theories in the research literature relating to the purchase intention in the food market. The aim of the paper is to determine what dominant theories and models found in the literature are used in the analysis of consumer behaviour relating to the purchase intention in the food market. It also seeks to examine research approaches and methods employed, as well as the authors’ perspectives on the applied theories or models, in order to highlight future opportunities for both qualitative and quantitative research in this area. The authors analyse 111 papers published in the years 2020–2023. The critical review has been adopted as a method of literature analysis. The results obtained indicate that the most frequently used theory or model in the consumer behaviour analysis regarding the food market is the Theory of Planned Behaviour (TPB). Nevertheless, in several studies, it is observed that the theories and models presented in the literature are used without providing any perspective or conclusion by the authors in this research area.